2021
DOI: 10.1186/s13046-020-01808-3
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of epithelial-mesenchymal transformation by hepatocellular carcinoma-educated macrophages through Wnt2b/β-catenin/c-Myc signaling and reprogramming glycolysis

Abstract: Background Tumour-associated macrophages (TAMs) in the tumour microenvironment (TME) can promote the progression of hepatocellular carcinoma (HCC). Some tumours can be suppressed by targeting Wnt2b in tumour cells. However, the role of Wnt2b in HCC is still unknown. In particular, the role of Wnt2b-mediated signal activation in macrophage polarization in the HCC microenvironment, and the regulatory effect between Wnt and glycolysis in TAMs has not been described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 64 publications
3
65
0
Order By: Relevance
“…1E). A large number of studies have con rmed that β-catenin promotes glycolysis by regulating the expression of glycolysis related genes (Fan et al 2018;Jiang et al 2021). In this study, MBP increased the expression of β-catenin (Fig.…”
Section: Dbp/mbp Promoted Glucose Metabolism In Scssupporting
confidence: 52%
“…1E). A large number of studies have con rmed that β-catenin promotes glycolysis by regulating the expression of glycolysis related genes (Fan et al 2018;Jiang et al 2021). In this study, MBP increased the expression of β-catenin (Fig.…”
Section: Dbp/mbp Promoted Glucose Metabolism In Scssupporting
confidence: 52%
“…As a result, the gene sets about metastasis and Wnt-related pathway regulators attracted our attention. Wnt/β-catenin signaling pathway was shown to be mainly involved in the Warburg effect and malignant progression of cancer cells ( 30 , 31 ). It was reported that Wnt/β-catenin signaling induced an increase in glucose uptake and suppressed mitochondrial respiration, mechanically activating pyruvate carboxylase to support cancer cells proliferation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the translocation of PKM2 into the nucleus could elevate β-catenin accumulation, afterward causing the expression of C-Myc ( David et al, 2010 ; Yang et al, 2011 ). Interestingly, the activation of Wnt/β-catenin signaling has been demonstrated to augment glycolysis via C-Myc in tumors ( David et al, 2010 ; Jiang et al, 2021 ). Hence, there may be a positive feedback loop between C-Myc and PKM2 to drive glycolysis and EMT.…”
Section: Discussionmentioning
confidence: 99%